Shoaling behaviour in the European cuttlefish Sepia officinalis. (8th September 2021) - Drerup, Christian; Cooke, Gavan M.
Abstract: Group living is a common behavioural feature in many different animal species. It offers a multitude of fitness benefits, such as increased opportunities to find resources, improved predator vigilance and potentially even social learning. In cephalopods, social grouping behaviour has mainly been reported for squid species, with up to several thousand individuals displaying different forms of shoaling and even schooling behaviour. Despite being held in groups in captivity, cuttlefish (Cephalopoda: Sepiidae) have long been considered rather asocial animals. However, reports of breeding aggregations and one recent schooling observation from the wild started to bring this characterisation into question. Following this, we here present 10 observations of the European cuttlefish Sepia officinalis (Linnaeus 1758) forming groups of up to 30 individuals along the South Coast of the UK. The majority of the observed cuttlefish appeared to be juveniles or subadults and showed different shoaling orientations, such as linear or spherical‐shaped formations. This indicated the grouping behaviour did not derive from coincidental accumulations. No mating or courtship behaviour could be identified in these groups, and as all observations were made in August or September, and therefore outside their mating season (March to June), it is unlikely that reproductive behaviour motivates these aggregations. As S. officinalis is known to migrate to deeper overwintering grounds in autumn, we propose that cuttlefish may temporarily form groups in late summer/early autumn as part of their migration pattern, and that their shoaling behaviour likely offers similar fitness benefits as in other migrating shoaling species. Abstract : Cephalopods of the family Sepiidae, commonly known as cuttlefish, have long been considered asocial. In this study, we report grouping behaviour of the European cuttlefish Sepia officinalis from the South Coast of the UK, with group sizes up to 30 individuals. All observed groups showed distinct shoaling behaviour previously reported for social squid species, such as (a) linear‐shaped formations with all individuals facing one direction expect one cuttlefish potentially acting as a sentinel by facing the other way, and (b) spherical formations with all cuttlefish facing outwards.